Computer-based safety training for semiconductor industry - Kamarrudin, Nadia; Ali, Mohamed Wijayanuddin; Kamsah, Mohd. Zaki; Hassim, Mimi Haryani; Kidam, Kamarizan (Penerbit UTM Press, 2009)
A computer-based safety training (CBT) for semiconductor industry using web as the platform was developed. The CBT system is called Sistem Latihan Keselamatan Berasaskan Komputer (SLK). The CBT system has two main sections which are safety theory modules and accident prevention scenarios. The survey conducted in semiconductor industry concluded that 86.7% of the respondents have successfully increased their safety awareness and understanding towards safety at workplace after studying the SLK system. The highest increment is about 46 % and the lowest is about 8%. SLK system was found to be a practical tool in the selected semiconductor industry and has successfully increased the awareness of safety procedures as well as the understanding of good working practices.